Sculpture with a Torch - Rood, John (Book collections on Project MUSE., 1968)
John Rood, a sculpture and former professor of art at the University of Minnesota, provides in this book a practical, how-to-do-it discussion of the technique of welded metal sculpture. In addition to serving as an instruction manual for students and arti.